Blood pressure trajectories and the mediated effects of body mass index and HIV‐related inflammation in a mixed cohort of people with and without HIV in rural Uganda - Okello, Samson; Kim, June‐Ho; Sentongo, Ruth N.; Tracy, Russell; Tsai, Alexander C.; Kakuhikire, Bernard; Siedner, Mark J. (The Journal of Clinical Hypertension, 2019)
We sought to describe changes in blood pressure and estimate the effect of HIV on blood pressure (BP) over 4 years of observation in a cohort of 155 HIV‐infected adults (≥40 years) on antiretroviral therapy (ART) and 154 sex‐ and age‐quartilematched, population‐based, HIV‐uninfected controls for four years in rural Uganda, we compared changes in blood pressure (BP) by HIV serostatus and tested whether body mass index and inflammation (high‐sensitivity C‐reactive protein and interleukin‐ 6) and immune activation (sCD14 and sCD163) mediated the effects of HIV on BP using hierarchical multivariate and two‐stage parametric regression models. Overall HIV‐uninfected participants had higher mean BP than HIV‐infected counterparts (differences in trend P < 0.0001 for diastolic BP and P = 0.164 for systolic BP). After initial declines in BP in both groups between years 1 and 2, BP moderately increased in both groups through year 4, with greater change over time observed in the HIVuninfected group. Body mass index mediated 72% (95%CI 57, 97) of the association between HIV and systolic BP. We found a minimal mediating effect of sCD14 on the relationship between HIV and SBP (9%, 95% CI 5%, 21%), but found no association between other HIV‐related biomarkers. Over four years of observation, HIV‐infected people in rural Uganda have lower BP than HIV‐uninfected counterparts despite having higher levels of inflammation. BMI, rather than measures of HIV‐associated inflammation, explained a majority of the difference in BP observed.
Keywords: Blood pressure trajectories; Body mass index; HIV; Rural Uganda